Enhancing Gastric Retention: A Novel Gastroretentive Drug Delivery System Utilizing Punica granatum and Jackfruit Seed as Polymer - Amruta V. Nawale; Apeksha C. Rahate; Madan D. Pomaje (The Bioscan, 2025)
Oral drug delivery is widely preferred for its ease of use, affordability, and patient compliance. However, challenges like enzymatic degradation, gastric pH variations, and inconsistent gastrointestinal transit can hinder drug absorption. Gastroretentive drug delivery systems (GRDDS), particularly floating drug delivery systems (FDDS), help overcome these issues by prolonging gastric retention and enabling controlled drug release. With the growing interest in phytopharmaceuticals, research has expanded into natural bioactive compounds. Pomegranate (Punica granatum L.) offers antiviral, antibacterial, antifungal, antioxidant, and anti-inflammatory benefits due to its polyphenol content. Jackfruit (Artocarpus heterophyllus Lam.) seeds contain bioactive compounds with anticancer, antihypertensive, and antiulcer properties, while also serving as a natural binder in formulations. This study explores the incorporation of pomegranate and jackfruit seed extracts into GRDDS, aiming to enhance drug bioavailability and therapeutic efficacy, contributing to the development of herbal-based pharmaceutical innovations. controlled release, Jackfruit, pomegranate